Diaspora Tourism For National Development From A Social Practice Theory Perspective: A Scoping Review - Heri Puspito Diyah Setiyorini; Caria Ningsih; Dewi Turgarini; Tingzhen Chen (Ministry of Tourism Republic of Indonesia, 2026)
Diaspora tourism has gained increasing attention in tourism studies. However, its contribution to national development remains fragmented. This study aims to reposition diaspora tourism as a strategic mechanism for national development. Social Practice Theory is used as a lens to examine the relationship between diaspora tourism and national development. A scoping review approach was adopted for analysing 143 abstracts from peer-reviewed journal articles. The study combines text mining and visualisation techniques using Voyant Tools with manual keyword categorisation to identify key research patterns. The findings show three interconnected clusters within diaspora tourism research: (1) heritage and cultural identity connections, (2) destination development potential, and (3) social engagement and social capital formation. Based on these findings, the study proposes a conceptual framework positioning diaspora tourism as a process that links meanings associated with identity and heritage, competences related to social engagement and social capital building, and materials reflected in the enabler of development outcomes, as in infrastructure, accessibility, and connectivity, as well as, governance and policy integration. This study contributes to the literature by reframing diaspora tourism as a strategic resource and highlighting its potential to support sustainable and participatory national development.